2023
DOI: 10.3389/fenvs.2023.1091203
|View full text |Cite
|
Sign up to set email alerts
|

The information transmission and risk contagion effect between green bond market and government bond market in China

Abstract: The problem of correlation between the Chinese green bond market and the government bond market may affect the smooth operation of the national economy. In this paper, a total of 3,181 sets of data representing the China’s green bond market and the government bond market for the period 2010–2022 are selected, and the VECM-DCC-VARMA-AGARCH model is used to analyse the spillover effects between the two in terms of information transmission and risk contagion. The results indicate that 1) The dynamic correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…If the U.S. adopts a tightening stance, it might be perceived as a response to domestic inflationary pressures or potential economic downturns. Such perceptions can induce global investors to seek safer assets, including Chinese government bonds, leading to changes in their yields [15].…”
Section: Analysis Of the Transmission Mechanismmentioning
confidence: 99%
“…If the U.S. adopts a tightening stance, it might be perceived as a response to domestic inflationary pressures or potential economic downturns. Such perceptions can induce global investors to seek safer assets, including Chinese government bonds, leading to changes in their yields [15].…”
Section: Analysis Of the Transmission Mechanismmentioning
confidence: 99%
“…Another study by Zhou et al (2023) analyzed information transmission and risk contagion between China's green bond market and its government bond market using advanced statistical models such as the VECM-DCC-VARMA-AGARCH model. Their results indicated that there's a significant dynamic correlation between these markets, with strong information transmission and risk contagion effects.…”
Section: Literature Reviewmentioning
confidence: 99%